Where less is more: institutional voids and business families in Sub-Saharan Africa. Issue 1 (7th February 2019) - Murithi, William; Vershinina, Natalia; Rodgers, Peter
Abstract : Purpose: The purpose of this paper is to offer a conceptual interpretation of the role business families play in the institutional context of sub-Saharan Africa, characterised by voids within the formal institutional setting. Responding to calls to take a holistic perspective of the institutional environment, we develop a conceptual model, showcasing the emergence of relational familial logics within business families that enable these enterprising organisations to navigate the political, economic and socio-cultural terrain of this institutional context. Design/methodology/approach: The authors undertake a review of extant literature on institutional theory, institutional voids, family business and business families and examine the relevance of these theoretical constructs in relation to the institutional environment of Sub-Saharan Africa. The authors offer tentative propositions within our conceptualisation, which the authors discuss in an inductive fashion. Findings: The review underlines the relevance of informal political, economic and socio-cultural institutions within the sub-Saharan context, within which the family as an institution drives business families engagement in institutional entrepreneurship. In doing so, the authors argue business families are best positioned to navigate the existing Sub-Saharan African institutional context. The authors underline the critical relevance of the embeddedness of social relationships that underpin relational familial logic within the sub-Saharan African collectivist socio-cultural system. Originality/value: By challenging the assumptions that institutional voids are empty spaces devoid of institutions, the authors offer an alternative view that institutional voids are spaces where there exists a misalignment of formal and informal institutions. The authors argue that in such contexts within Sub-Saharan Africa, business families are best placed to harness their embeddedness within extended family and community for entrepreneurial activity. The authors argue that family and business logics may complement each other rather than compete. The discussions and propositions have implications for future research on business families and more inclusive forms of family organisations.